X RUSSIAN SCIENTIFIC CONFERENCE WITH INTERNATIONAL PARTICIPATION "REHABILITATION AND SECONDARY PREVENTION IN CARDIOLOGY", MAY 18-19, 2011, MOSCOW (Столичная издательская компания, 2016)
X Russian scientific Conference with International Participation "Rehabilitation and Secondary Prevention in Cardiology", May 18-19, 2011, Moscow.